1996
DOI: 10.1021/ac960461w
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Detection of Flavonols in HPLC by Postcolumn Chelation with Aluminum

Abstract: Flavonols are dietary antioxidants which may prevent coronary heart disease. To be able to study absorption of flavonols in humans, we developed a postcolumn derivatization with aluminum for HPLC with fluorescence detection. Variables governing postcolumn chelation, such as water content, buffer, organic modifier of the eluent, concentration of Al(3+), presence of acetic acid in the postcolumn reagent, and temperature, were studied and optimized. Of the flavonoids, only flavonols that contain a free 3-hydroxyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
78
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 145 publications
(84 citation statements)
references
References 17 publications
6
78
0
Order By: Relevance
“…The quercetin concentration in plasma peaked 2 h after ingestion at 248.4 AE 103.9 ngaml (Figure 1), corresponding to a plasma quercetin concentration of 0.73 AE 0.30 mM, and then decreased, returning to baseline levels 24 h after ingestion. These results are comparable to those of Hollman et al (1996) in a similar study where two subjects consumed 215 g of fried onions.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The quercetin concentration in plasma peaked 2 h after ingestion at 248.4 AE 103.9 ngaml (Figure 1), corresponding to a plasma quercetin concentration of 0.73 AE 0.30 mM, and then decreased, returning to baseline levels 24 h after ingestion. These results are comparable to those of Hollman et al (1996) in a similar study where two subjects consumed 215 g of fried onions.…”
Section: Discussionsupporting
confidence: 88%
“…However, more recently, using more accurate analysis techniques, Hollman et al (1995) demonstrated that 24% of orally administered quercetin aglycone was absorbed. In a further study they found the quercetin glucosides present in onions were shown to be absorbed even more ef®ciently than the aglycone (Hollman et al, 1996).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations